The exéresis glandular - Gary, Ruben (Cirugía del Uruguay, 1973)
The author examines two important chapters: a) surgical exploration and topographic pathological anatomy of goiter; and b) abscission of parenchima. After :malyzing the abnormal anatomical relationship of the augmented gland he reviews and studies different manners of resencting pathological thyroid and the extension of a escission according to type of lesion.